Enhancement of double-layer capacitance behavior and its electrical conductivity in layered poly (3, 4-ethylenedioxythiophene)-based nanocomposites - Murugan, A. Vadivel; Viswanath, A. K.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Applied Physics Letters, 2005)
In this letter, we report on the enhanced double-layer capacitance of a layered poly (3, 4-ethylene dioxythiophene) PEDOT-MoO3 nanocomposite, which has been synthesized by a novel microwave irradiation method. The x-ray photoelectron spectroscopy analysis shows the changes in electron density and the shift in binding energy suggesting charge transfer from sulfur atoms upon PEDOT intercalation between MoO3 layers. The room-temperature conductivity for the PEDOT-MoO3 composite is found to be 1.82x10(-1) S cm(-1), which is four orders of magnitude higher than that of the pristine oxide (3.78x10(-5) S cm(-1)). The enhanced double-layer capacitance of the PEDOT-MoO3 nanocomposite (similar to 300 F g(-1)) compared to that (similar to 40 mF g(-1)) of pristine MoO3 is attributed to higher electronic conductivity, enhanced bidimensionality, and increase in surface area of the nanocomposite.

Unusual formation of nano-particles of CdO and Cd(OH)(2) from the reaction of dimethyl cadmium with DMF - Singh, Narendra; Charan, Shobhit; Patil, K. R.; Viswanath, A. K.; Khanna, P. K. (Materials Letters, 2006)
This paper presents generation of CdO and Cd(OH)(2) nano-particles from Dimethyl Cadmium in DMF. The CdO nano-particles were obtained instead of CdSe, even when the reaction was done in presence of 1,2,3-selenadiazole (the source of selenium) with Me2Cd in DMF (product-I). The direct reaction of Me2Cd in DMF also leads to formation of CdO (product-II). However, Cd(OH)(2) nano-particles were obtained when Me2Cd was refluxed in DMF for a few hours followed by reaction of H2S gas (product-III). The formation of Cd(OH)(2) was also established via decomposition Of Me2Cd:Et2O adduct (product-IV). Nano-particles of CdO and Cd(OH)(2) (product-I to product-IV) were characterized by X-ray powder diffraction (XRD), TEM and SEM/EDS measurements, FTIR, thermal analysis (TGA) and XPS analysis. The particle size of all the products as calculated by XRD patterns were in the range of about 20 nm. TEM images showed that the products are agglomerated clusters with the particles in the nano-meter regime. The synthesis however, is understood to be unusual as the reactions with selenium source and sulfur source should have generated the CdSe and CdS however, the end products were always found to be the product-I to product-IV (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Nanoparticles; Semiconductor; XRD